Costos de producción de mango orgánico en la zona de Chacras - San Martín Ruiz, Daniel Eloy (2007)
The present work was carry out in “the three maries” farm. It’s located in chacras village, Arenillas town. The objectives were: 1. Determinate the production cost of the organic mango grow. 2. Obtain the profita-bility border of this product, focus the producción cost and the in-gresses obtained. 3. Have the information actuality of organic mango exportation. Was determinate the production cost of 30 hectares that was 26.959,30 dollars, by hectare of 898,64 dollars and by unit of 4kilograms produced od 1,28 dollars, with a production of 21.000 boxes. At the same time was obtained the sell ingreses in 2,40 dollars each box of 4 kg giving the total of 50.400 dollars. The total produc-tion profitability i 23.440,70 dollars it’s the diference result total in-gresses sell ess the total production cost. The profitability border by unit produced is determinated of the diference between the 4 kg. box cost of organic mango and the production cost by unit giving a total of 1,12 dollars. The rentability is determinatated of divided by the profit-ability border produced by unit to the production cost by unit; this is times by 100 it’ll give us the rentability percent that is 87,5%.